Paper-based and computer-based concept mappings: The effects on computer achievement, computer anxiety and computer attitude - ERDOĞAN, YAVUZ (WILEY, 2009)
The purpose of this paper is to compare the effects of paper-based and computer-based concept mappings on computer hardware achievement, computer anxiety and computer attitude of the eight grade secondary school students. The students were randomly allocated to three groups and were given instruction on computer hardware. The teaching methods used for each group were the conventional method, paper-based concept mapping and computer-based concept mapping. At the end of a 4-week instruction, posttests were administered to assess computer hardware achievement, computer anxiety and computer attitude of the students. The findings indicate that paper-based and computer-based concept mapping strategies produce better results than the conventional method. However, the effects of paper-based and computer-based concept mapping strategies were not significantly different.
Keywords: STUDENTS